Perlindungan Hukum Tenaga Kerja Terhadap Pemutusan Hubungan Kerja Dalam Masa Pandemi Covid-19 Menurut Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan - Amiruddin, Alifiya Mafaza; Sugiyono, Heru (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2023)
Abstract This study was conducted to determine the legal arrangements for termination of employment by employers who experienced the impact of Covid-19 on workers according to labor laws and legal protection of workers who experienced termination of employment by employers who were affected by Covid-19. This study uses normative juridical research methods. Legal protection for workers experiencing termination of employment during the Covid-19 pandemic until now there is still a lack of explicit efforts to heed workers' rights from employers to implement the provisions of the law. Since the issuance of Presidential Decree (Keppres) No.12 of 2020 concerning Determination of Non-Natural Disasters Spread of Corona Virus Disease 2019 (Covid-19) As National Disasters employers certainly have reason to terminate employment in the face of this pandemic in terms of the state of the company. Legal provisions for termination of employment are regulated in Act Number 13 of 2003 concerning Manpower. The impact of employment due to this pandemic on employment relations that led to termination of employment due to the closure of the company, the Work From Home work system, causing unemployment. Keywords: Legal Protection, Work Termination, Employment, Covid-19